2019
DOI: 10.1029/2019gl083732
|View full text |Cite
|
Sign up to set email alerts
|

Strength Profile of the Inner Nankai Accretionary Prism at IODP Site C0002

Abstract: The strength of accretionary prisms is important for understanding their formation and the generation of earthquakes along the underlying plate boundary faults. We establish a continuous depth profile of rock strength and possible ranges of the minimum and maximum horizontal stresses (Shmin and SHmax) based on indentation tests on cuttings samples at the Integrated Ocean Drilling Program (IODP) Site C0002 in the Nankai accretionary prism. The rock strength (i.e., differential stress) increases with depth from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…When we combined the C 0 values determined in this study with C 0 depth profile data for Site C0002 reported by Kitamura and Hirose (2017) (Figure 5c), we found that, overall, the estimated C 0 values in Holes C0002N and C0002P tended to increase with depth, from ∼0.9–1.5 MPa at ∼1,000 mbsf to ∼11 MPa at ∼3,000 mbsf (see details in Kitamura et al., 2019). C 0 values in Holes C0002Q–S, estimated in this study, stayed in range between 3.1 and 18.2 MPa, at 2,822–3,262 mbsf (data with error bars in Figure 5c).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…When we combined the C 0 values determined in this study with C 0 depth profile data for Site C0002 reported by Kitamura and Hirose (2017) (Figure 5c), we found that, overall, the estimated C 0 values in Holes C0002N and C0002P tended to increase with depth, from ∼0.9–1.5 MPa at ∼1,000 mbsf to ∼11 MPa at ∼3,000 mbsf (see details in Kitamura et al., 2019). C 0 values in Holes C0002Q–S, estimated in this study, stayed in range between 3.1 and 18.2 MPa, at 2,822–3,262 mbsf (data with error bars in Figure 5c).…”
Section: Resultssupporting
confidence: 58%
“…Although Kitamura et al. (2019) suggested that the strength of cuttings, as determined by indentation tests, showed little dependence on lithology above ∼3,000 mbsf in Holes C0002N and C0002P, we found that between 2,822 and 3,262 mbsf in Holes C0002Q–S, the C 0 values of sandy materials determined in this study tended to be higher than those of silty or clayey materials, except for two high C 0 values of siltstone from 2,822 and 2,862 mbsf in Hole C0002R.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation